THE INFLUENCE OF ELECTRONIC WORD OF MOUTH AND PERCEIVED QUALITY TOWARDS PURCHASE DECISION ON PINK FLASH PRODUCT (STUDY ON GEN Z SOCIAL MEDIA USER) - Rondonuwu, Happy Estherella; Lapian, S. L. H. V. Joyce; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study investigates the influence of electronic word of mouth and perceived quality towards purchase decisions on Pink Flash Product (study on gen Z social media user). Utilizing a quantitative research approach, the study employed a non-probability sampling method through purposive sampling, with 100 respondents participating in the survey. The analysis reveals that while electronic word of mouth does not exert a significant partial influence on purchase decisions independently, perceived quality demonstrates a significant partial influence. However, both factors collectively have a simultaneous and significant influence on Purchase Decisions. These findings underscore the critical role of perceived quality in shaping consumer choices, while highlighting the need for more nuanced strategies to leverage EWOM effectively. The study contributes to a deeper understanding of the dynamics between digital marketing factors and consumer behavior among Gen Z.   Keywords: Electronic Word Of Mouth, Perceived Quality, Purchase Decision